GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1823 species occurrences available in GBIF matching the query: TaxonKey: Tripleurospermum inodorum (L.) Sch.Bip. HasCoordinate: true HasGeospatialIssue: false BasisOfRecord: Specimen. The dataset includes 1823 records from 89 constituent datasets: 20 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 13 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 3 records from Phanerogamic Botanical Collections (S). 5 records from Naturalis Biodiversity Center (NL) - Botany. 7 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 2 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 23 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 41 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 1 records from Herbario Museo de La Salle Bogotá (MLS). 167 records from OHN. 46 records from Australia's Virtual Herbarium. 34 records from Vascular Plant Herbarium, UiB. 18 records from Kathryn Kalmbach Herbarium. 3 records from Consortium of California Herbaria. 7 records from CONN. 1 records from H.A. Stephens Herbarium. 2 records from Estonian Museum of Natural History. 1 records from Collection botanique Le Grand A. (BOUM). 19 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 2 records from Estonian University of Life Sciences. 14 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 8 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 55 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 1 records from Collection botanique Mulon L. (BOUM). 20 records from Tiroler Landesmuseum Ferdinandeum. 13 records from Tropicos Specimen Data. 27 records from Natural History Museum (London) Collection Specimens. 5 records from Natural History Museum, Vienna - Herbarium W. 5 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 1 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 1 records from ANTARCTIC PLANT DATABASE. 1 records from Canadian Museum of Nature Herbarium. 14 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 2 records from Herbarium (ICEL). 2 records from Herbarium (AMNH). 1 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 4 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 5 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 3 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 1 records from Aranzadi Zientzi Elkartea. 1 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 1 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 6 records from Institut Botanic de Barcelona, BC. 8 records from Auckland Museum Botany Collection. 102 records from Herbarium of Jyväskylä University Museum. 2 records from Plant Specimens of Kurashiki Museum of Natural History. 1 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 9 records from Vascular Plant Collection. 9 records from Herbarium Berolinense. 3 records from Observations du Conservatoire botanique national du Bassin parisien.. 2 records from Institut Botanic de Barcelona, BC-Histórico. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 12 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 13 records from Colorado State University Herbarium. 1 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from EDIT - ATBI in Gemer area (Slovakia). 1 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 18 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 2 records from Gunma Museum of Natural History, Vascular Plant Specimen. 1 records from Jardín Botánico Atlántico, Gijón: JBAG. 1 records from Biological and palaeontological collection and observation data MNHNL. 10 records from Herbarium Senckenbergianum (FR). 2 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 15 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 1 records from Vascular Herbarium, NMBU. 2 records from Flora d'Andorra. 390 records from Lund Botanical Museum (LD). 16 records from Norwegian Species Observation Service. 2 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 14 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 6 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 1 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 24 records from Vascular plant herbarium, Tromsø Museum. 66 records from Vascular plant herbarium, NTNU University Museum. 1 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 26 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 1 records from Green Plant Herbarium (TRT). 2 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 20 records from Allan Herbarium (CHR). 6 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 259 records from Vascular Plant Herbarium, Oslo (O). 5 records from E. C. Smith Herbarium (ACAD). 142 records from Vascular plant field notes, NTNU University Museum. 13 records from Instituto de Botánica Darwinion. 1 records from UFMT - Herbário UFMT. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences